The Risk of Paradoxical Embolism (RoPE) Study: initial description of the completed database. Issue 8 (9th August 2012) - Thaler, David E.; Di Angelantonio, Emanuele; Di Tullio, Marco R.; Donovan, Jennifer S.; Griffith, John; Homma, Shunichi; Jaigobin, Cheryl; Mas, Jean‐Louis; Mattle, Heinrich P.; Michel, Patrik; Mono, Marie‐Luise; Nedeltchev, Krassen; et al.
<x xml:space="preserve">Abstract</x> Background Detecting a benefit from closure of patent foramen ovale in patients with cryptogenic stroke is hampered by low rates of stroke recurrence and uncertainty about the causal role of patent foramen ovale in the index event. A method to predict patent foramen ovale‐attributable recurrence risk is needed. However, individual databases generally have too few stroke recurrences to support risk modeling. Prior studies of this population have been limited by low statistical power for examining factors related to recurrence. Aims The aim of this study was to develop a database to support modeling of patent foramen ovale‐attributable recurrence risk by combining extant data sets. Methods We identified investigators with extant databases including subjects with cryptogenic stroke investigated for patent foramen ovale, determined the availability and characteristics of data in each database, collaboratively specified the variables to be included in the Risk of Paradoxical Embolism database, harmonized the variables across databases, and collected new primary data when necessary and feasible. Results The Risk of Paradoxical Embolism database has individual clinical, radiologic, and echocardiographic data from 12 component databases, including subjects with cryptogenic stroke both with (n = 1925) and without (n = 1749) patent foramen ovale. In the patent foramen ovale subjects, a total of 381 outcomes (stroke, transient ischemic attack, death) occurred (median follow‐up 2·2 years). While there were substantial variations in data collection between studies, there was sufficient overlap to define a common set of variables suitable for risk modeling. Conclusion While individual studies are inadequate for modeling patent foramen ovale‐attributable recurrence risk, collaboration between investigators has yielded a database with sufficient power to identify those patients at highest risk for a patent foramen ovale‐related stroke recurrence who may have the greatest potential benefit from patent foramen ovale closure.